2012
DOI: 10.3748/wjg.v18.i27.3571
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and clinicopathologic characteristics of early gastric cancer with high microsatellite instability

Abstract: MSI-H EGC is associated with unique endoscopic and clinicopathologic characteristics including frequent presentation in protruded type, co-existing underlying adenoma, and synchronous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Finally, a study investigating clinicopathological and molecular features between MLH1 methylation‐positive and ‐negative MSI gastric cancers was not included. Forty‐eight studies published between 1994 and 2016, with a study interval ranging from 1980 and 2013, were included in the review ( Table S2 , supporting information). The total number of patients included was 18 612, ranging from 24 to 2959 per study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a study investigating clinicopathological and molecular features between MLH1 methylation‐positive and ‐negative MSI gastric cancers was not included. Forty‐eight studies published between 1994 and 2016, with a study interval ranging from 1980 and 2013, were included in the review ( Table S2 , supporting information). The total number of patients included was 18 612, ranging from 24 to 2959 per study.…”
Section: Resultsmentioning
confidence: 99%
“…Five of 48 studies (637 patients, 3·4 per cent) were multicentre studies from the USA, Canada, Germany, Korea, Poland, Russia, Ukraine, Vietnam, the UK, South Africa, Chile, Colombia and Japan. The other 43 studies were performed in single centres in Eastern populations (15 529 patients, 83·4 per cent) from Japan, China, Korea and Taiwan, or in Western populations (2446 patients, 13·1 per cent) from Italy, Poland, Slovenia, the UK, Portugal, Brazil and Germany.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with negative PTEN expression had worse median overall survival than patients with positive PTEN expression ( Figure 3B, p < 0.001). To further find out the risk factor affecting the survival rate of patients, patients were divided into four groups as four different [17]. Moreover, Arai et al showed that much higher amount of cases with MSI were observed with poorly differentiated gastric adenocarcinoma than other subtypes [18].…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of inactivating mutations and deletions of both alleles of a tumor suppressor gene was involved in the process of carcinogenesis. Loss of heterozygosity (LOH) may increase cancer susceptibility, particularly following exposure to environmental carcinogens (9).…”
Section: Introductionmentioning
confidence: 99%